Constructing the canon of children's literature : beyond library walls and ivory towers - Lundin, Anne H., 1944- (Children's literature and culture., 2004)
In this pioneering historical study, Anne Lundin argues that schools, libraries, professional organizations, and the media together create and influence the canon of childrens literature.